Endometrial changes during ulipristal acetate use: A systematic review. (July 2017) - De Milliano, Inge; Van Hattum, Dominique; Ket, Johannes C.F.; Huirne, Judith A.F.; Hehenkamp, Wouter J.K.
Abstract: Ulipristal acetate is increasingly used for several clinical indications, like emergency contraception and pre-treatment of uterine fibroids. It has mixed progesterone agonist and antagonist effects in the myometrium and endometrium. Due to its progesterone antagonistic effect, an unopposed estrogen effect could occur which could cause (pre-)malignant lesions in the endometrium. Several studies have been performed to evaluate this possible increased risk for endometrial malignancies when using ulipristal acetate. The specific spectrum of morphological changes due to ulipristal acetate, named progesterone receptor modulator associated endometrial changes (PAEC), occurs to be reversible after discontinuing ulipristal acetate. In this systematic review we provide a detailed overview of the literature on histopathological endometrial changes and imaging characteristics of the endometrium in ulipristal acetate users. We performed an extensive search in Embase.com, Wiley/Cochrane Library and PubMed in accordance with the prisma guidelines. All studies published as full papers in peer reviewed journals using ulipristal acetate reporting on endometrial changes were included, independent of clinical indication, dosage taken and duration of therapy. No language restrictions were applied. Ten studies with a total of 1450 participants were included. Seven were randomized clinical trials and three prospective cohort studies. A quality assessment of all included studies was performed. In only five of ten studies an endometrial biopsy was performed during treatment. All of these studies described specific histological non-physiological endometrial changes (PAEC) due to ulipristal acetate, varying from 41 to 78.8% of all patients. Three of these studies also performed follow-up biopsies after discontinuing ulipristal acetate. The percentage of PAEC decreased from 62% to 0%, 78.8% to 0% and from 59% to 6–7% after the treatment period. In six of 1450 women (0.4%) endometrial hyperplasia was reported during or after ulipristal acetate use. Five were simple hyperplasia, one biopsy showed simple atypical endometrial hyperplasia that resolved into benign secretory endometrium by the end of the treatment. One case of endometrial adenocarcinoma was reported, however this does not seem to be related to ulipristal acetate use, since it was already present at the baseline biopsy. In eight of ten studies a transvaginal ultrasound or MRI was performed at any moment to assess the endometrial thickness before, during and after treatment. Most studies showed a transient increase of endometrial thickness during treatment, which returned to normal within a few weeks after discontinuing ulipristal acetate. Based on the literature found in this systematic review, follow-up after a maximum of four courses of ulipristal acetate did not report any non-reversible (pre-)malignant lesions of the endometrium. Most studies focused on short term use of ulipristal acetate and their follow-up period was limited. Therefore, we believe more information concerning long term (intermittent) use is needed before it can be concluded that its use is completely safe.